Formação continuada de professores de matemática na perspectiva do ensino híbrido - Almeida, Adriana Neves de (2017)
This research presents discussions about the continuing education of Mathematics teachers and Blended Teaching, as aspects that correlate to the teacher pedagogical process. The research purpose was to understand in which aspects a continuing education course, based on Blended Teaching, can contribute to the pedagogical process of Mathematics teachers regarding to the reflection of the pedagogical practice itself. Considering this purpose, the research participants were six professors who work in Technical Professional Education of Medium Level and in Higher Education. It is a qualitative research, in which the action research was used as a strategy for its development, it was structured in three phases: formative actions planning, implementation and evaluation. Regarding the techniques and instruments for the data production, the following were used: conversation wheel and observation; field day-book, audio recordings, questionnaires and teacher’s productions during the course. The research data were organized and interpreted through Discursive Textual Analysis, and showed that continuing education is primordial for the teacher pedagogical development and to the teaching and learning process. They also demonstrated that technologies are allied to the teacher in teaching practices; giving dynamism to his work in the classroom. The results indicate that it is necessary that the educational institutions encourage the formative processes in the school context, considering the particularities of the knowledge areas based on the reality lived by the teacher. Concerning the pointed aspects of the continuing education course contribution for the reflection of the pedagogical practice itself of the Mathematics teachers, research participants, it can be highlighted: the planning importance for the teaching actions organization in the classroom; understanding that technologies can support the teaching and learning process; teacher’s reflection as a classroom manager; and finally, the recognition of the relevance of continuing education for the pedagogical process and pedagogical practice improvement.